Decomposition of Microbial Necromass Is Divergent at the Individual Taxonomic Level in Soil - Dong, Weiling; Song, Alin; Yin, Huaqun; Liu, Xueduan; Li, Jianwei; Fan, Fenliang (Frontiers in Microbiology, 2021)
The turnover of microbial biomass plays an important part in providing a significant source of carbon (C) to soil organic C. However, whether the decomposition of microbial necromass (non-living microbial biomass) in the soil varies at the individual taxa level remains largely unknown. To fill up these gaps, we compared the necromass decomposition of bacterial and archaeal taxa by separating live microbial biomass with 18O-stable isotope probing from dead microbial biomass in soil. Our results showed that most of the microbial necromass at OTU level (88.51%) which mainly belong to Acidobacteria, Actinobacteria, Gemmatimonadetes, and Proteobacteria decomposed significantly after 30 days. In addition, there were great variations in necromass decomposition within each phylum, such as the decomposition of OTUs in Proteobacteria ranged from 51% (Beijerinckia) to 92% (Nitrosospira). More importantly, the necromass decomposition was not related to the chemical composition of the cell wall, but might positively correlated with the GC content of DNA and negatively correlated with genome size. This study provided a new insight that the decomposition of microbial necromass in soil was divergent at the individual taxonomic level and could not be fully explained by previously proposed mechanisms.